Modelo de gestión para fomentar el turismo rural en la zona centro de Manabí - Mendoza Torres, María Cristina (2017)
The main objective of the research was to design a tourism management model to promote rural tourism in the central area of the province of Manabí. The research is descriptive-exploratory in nature with a qualitative approach. First he referred to the diagnosis of tourism management; Which was based on the description of the territory under study; In addition to obtaining criteria offered by the actors involved, was established through the application of the matrix of stakeholders and interviews directed to the main actors; In addition, the array of tourist potentialities and the SWOT matrix were developed; Which helped to obtain as a primordial result the information of the current management that carry each one of the tourist undertakings and territories framed in the investigation. The second objective was to determine the indicators of sustainable management, through the matrix of indicators with the help of bibliographical review and direct observation, having as reference the Biosphere certification and the global criteria of sustainable tourism acquiring the necessary guidelines for Lead an adequate process of sustainability. The third objective was established in structuring the strategy matrix and later detailed the operability of the actors in the tourist destinations; Carrying the evaluation and control of the activities and process to be executed; Establishing the expert method with the intention of providing optimum results in the proper planning during the management of each rural tourist destination.